Excreted/Secreted Proteins from Trypanosome Procyclic Strains. (30th November 2009) - Atyame Nten, Celestine Michelle; Sommerer, Nicolas; Rofidal, Valerie; Hirtz, Christophe; Rossignol, Michel; Cuny, Gerard; Peltier, Jean-Benoit; Geiger, Anne
Abstract : Trypanosoma secretome was shown to be involved in parasite virulence and is suspected of interfering in parasite life-cycle steps such as establishment in the Glossina midgut, metacyclogenesis. Therefore, we attempted to identify the proteins secreted by procyclic strains of T. brucei gambiense and T. brucei brucei, responsible for human and animal trypanosomiasis, respectively. Using mass spectrometry, 427 and 483 nonredundant proteins were characterized in T. brucei brucei and T. brucei gambiense secretomes, respectively; 35% and 42% of the corresponding secretome proteins were specifically secreted by T. brucei brucei and T. brucei gambiense, respectively, while 279 proteins were common to both subspecies. The proteins were assigned to 12 functional classes. Special attention was paid to the most abundant proteases (14 families) because of their potential implication in the infection process and nutrient supply. The presence of proteins usually secreted via an exosome pathway suggests that this type of process is involved in trypanosome ESP secretion. The overall results provide leads for further research to develop novel tools for blocking trypanosome transmission.